Programming an RTS game with Direct3D - Carl Granberg (Charles River Media, 2007)
There are many books that teach the basics of Direct3D, but few of these books teach and apply the more advanced topics needed to program complete applications such as games. Programming an RTS Game with Direct3D is such a reference. The book provides intermediate programmers with a step-by-step implementation guide for programming a complete RTS game. And, unlike other books that teach basic game programming, this book teaches programmers how to implement the more challenging parts of an RTS game, including advanced topics such as Skinned Meshes, Fog-of-war implementation, Team-color pixel shaders, AI, networking, and much more. The game is developed from chapter to chapter, beginning with design and storyboards through the development of a fully implemented RTS game, complete with Multi-Tier AI and Networking. This is a must-have resource for intermediate game programmers who wish to increase their skills and learn the more advanced topics required in todays commercial games